Pilgrimage as a phenomenon in the religious life of individuals and society in Western Europe during the Middle Ages (based on materials from foreign historiography) - Malishev, Dmitrii Arkad'evich (Genesis: исторические исследования, 2025)
The article analyzes pilgrimage as a phenomenon in the religious life of individuals and society in Western Europe during the Middle Ages. The author deliberately resorts to such geographical localization because the primacy in the process of Christianization in Western Europe was indisputable, and this part of the continent was almost half a millennium ahead of the European barbarians in the East and North. The experience of the Western European pilgrim has a greater chronological span and richer material for study. The research represents a comparative approach based on the study of foreign scientific experience. The author refers to the experience of English-speaking publications, attempting to study pilgrimage as a European phenomenon through the main stages of historical development in the region. According to the researcher’s intention, the article is part of a future trilogy of historical works dedicated to this issue. Using historical-genetic, comparative-historical, and interdisciplinary approaches, the author conducts a systematic study of pilgrimage in the everyday life of people in medieval Europe. The methodology of the research takes its specificity into account. The author works more with historiographical facts than with historical ones, which shifts the focus towards historiography, transforming each studied unit into a source. The author of the article makes the first attempt in Russian historiography to study and summarize the Western Christian experience of pilgrimage, including in works that indirectly touch on this issue. Such an approach undoubtedly adds novelty to the research, considering the introduction into the domestic historiographical discourse and historical information field of information from studies that are not always accessible due to language barriers and publishing policies. The author concludes that pilgrimage as a phenomenon is exclusively connected with Abrahamic religions. In terms of logistics, it includes primary - Palestinian - and secondary - local - routes. Western European pilgrims after the Great Schism of 1054 did not exclude Eastern Christian shrines from their points of visit. The Crusades have a genetic affinity with individual pilgrimages. Pilgrimage led to a partial Easternization of Western Europe in a socio-cultural dimension. The work may be useful for all those interested in the history of Christianity and pilgrimage, having a practical focus that can benefit people engaged in travel and the formation of logistics for routes in religious tourism.